2007
DOI: 10.1159/000106570
|View full text |Cite
|
Sign up to set email alerts
|

Kognitiv-psychoedukative Gruppenintervention bei stationären Patienten mit depressiven Erkrankungen – Ergebnisse einer prospektiven Pilotstudie

Abstract: Psychoeducational interventions that provide disorder-related information in a goal-oriented and structured manner have been integrated in psychiatric and psychotherapeutic approaches. The present cognitive psychoeducational group programme for inpatients with affective disorders is based on a multidimensional functional illness concept which covers aspects of vulnerability, stressors and coping strategies. It covers information about the disorder and its treatment options, building up rewarding activities, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This has yielded hope that meaningful recovery from schizophrenia [79][80][81] is possible and that patients can learn to improve the course of their illness. Education about schizophrenia, bipolar disorder, and depression and teaching effective self-help strategies [75][76][77][78][79][80][81] is now widely accepted as a treatment standard. Illness management programs also include cognitive behavioral interventions, such as teaching coping strategies, instilling hope by reframing challenging experiences and setting goals, supporting treatment adherence, and providing groups for relatives that enhance social networks and reduce relapse rates.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has yielded hope that meaningful recovery from schizophrenia [79][80][81] is possible and that patients can learn to improve the course of their illness. Education about schizophrenia, bipolar disorder, and depression and teaching effective self-help strategies [75][76][77][78][79][80][81] is now widely accepted as a treatment standard. Illness management programs also include cognitive behavioral interventions, such as teaching coping strategies, instilling hope by reframing challenging experiences and setting goals, supporting treatment adherence, and providing groups for relatives that enhance social networks and reduce relapse rates.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…42 Studies conducted in this hospital have demonstrated the feasibility, effectiveness, and efficacy of illness management group programs in patients with psychiatric illness. [75][76][77][78][79][80][81] Therapeutic interventions are also important for children (under the age of 18) who have parents with a psychiatric illness. 51 The interventions inform the children about the illness in a manner consistent with their developmental age, and seek to enhance their self-confidence and self-efficacy, both of which are important protective factors.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a control group limits the conclusions that can be drawn from this study. [30,[32][33][34] or outpatients with severe acute, partially remitted or chronic forms of depression (e.g., Keller et al and Teasdale et al [3,6] indicating that the combination of pharmacotherapy with psycho therapeutically interventions has a beneficial effect. It is associated with higher improvement, satisfaction with treatment and treatment adherence with pharmacotherapy than drug treatment alone [21,22,56].…”
Section: Discussionmentioning
confidence: 99%
“…Participating in interpersonal Schramm et al [30], cognitive Stuart and Bowers [31] or cognitive-psycho educational programs Schaub et al [12,32] led to high satisfaction with treatment and knowledge of depression as well as symptom reductions which were even maintained at six-month follow-up Backenstrass et al [33]. Only two controlled studies showed no or only little short-term benefits of combining pharmacotherapy with cognitive therapy compared to each condition only Hautzinger et al [34] or to the combination with supportive therapy De Jong-Meyer et al [35], however, there was some evidence for long-term effects.…”
Section: Introductionmentioning
confidence: 99%